Estimating energy price elasticities when salience is high: Residential natural gas demand in Ukraine - Anna Alberini; Olha Khymych; Milan Ščasný (Charles University in Prague, Institute of Economic Studies (IES), 2019)
Despite its importance for policy purposes (including climate policy and the energy transition), evidence about the price elasticity of natural gas demand in the residential sector is very limited and based on inference from situations with modest variation in prices. We focus on a locale and time when price changes were extreme and presumably salient to consumers, namely Ukraine between 2013 and 2017. We exploit the tariff reforms and detailed micro-level household consumption records to estimate the price elasticity of the demand for natural gas. To isolate behavior, attention is restricted to those households that made no structural energy-efficiency upgrades to their homes, and thus kept the stock of gas-using capital fixed. We further examine the short-run elasticity by restricting the sample to a few months before and after the tariff changes. Our results suggest that under extreme price changes, households are capable of reducing consumption, even without installing insulation or making any other structural modifications to their homes. The price elasticity is about -0.16. Wealthier households, people living in multifamily buildings, and heavy users have more inelastic demands. Households reduced consumption even when they received "subsidies," namely lump-sum government assistance, suggesting that when the price signal is sufficiently strong, lump-sum transfers have only a minimal effect on consumption. We also find some evidence that the stronger the salience, the stronger the responsiveness to price, although this effect is modest and may partly overlap with that of income or baseline consumption. Our data also suggest that the consumers with the lowest uptake of energy efficiency improvements might be those who−by necessity or through skills−are the most productive at reducing energy use through behaviors.
Keywords: D12; Q41; Q48; H31; 330; Residential gas demand; energy transition; short-run price elasticity; tariff reforms; salience; fuel poverty